Sosialisasi Potensi Daging Kelinci sebagai Sumber Protein Hewani dalam Pemenuhan dan Perbaikan Gizi Masyarakat: Sebagai Bagian dari Upaya Pengentasan Stunting - Alhuur, Ken Ratu gharizah; Sinaga, Sauland (Farmers: Journal of Community Services, 2025)
Reducing stunting rates remains a priority for the Indonesian Government, and this effort needs to be supported by the availability and affordability of food products. One potential animal-based food product that can improve nutritional fulfillment and enhancement for the community is rabbit meat. Its high nutritional content, rapid production rate, and high reproductive capacity make rabbit meat a potential alternative for meeting community nutritional needs. However, this requires community awareness of nutrition and knowledge of rabbit husbandry practices. Additionally, societal stigma surrounding the consumption of rabbit meat needs to be addressed, so that rabbit meat can be positioned alongside other commonly consumed meats like chicken and beef. This community service activity was conducted online with participants from animal husbandry, veterinary, and nutrition science backgrounds. Evaluation data was collected from pre-test and post-test results completed by participants. The benefits of this activity include increased participant awareness of the potential of rabbit livestock as a source of animal protein for the community, as well as its business potential. This activity is essential to conduct periodically with different participant segments to disseminate the information widely.